Digital Neuroethics and the Reconstruction of the Epistemology of Islamic Religious Education - Neyla Sabrina; Muhammad Thalal; Wulan Juliarti; Sonia Isna Suratin (Journal of Contemporary Islamic Education, 2025)
The posthuman era is marked by the integration of artificial intelligence, biotechnology, and digital systems that transform educational epistemology. Digitalization gives rise to algorithmic disinformation and knowledge manipulation, thus demanding an adaptive reconstruction of the epistemology of Islamic Religious Education based on reflective ethics. This study aims to analyze the Digital Neuroethics paradigm as a conceptual basis for the reconstruction of the epistemology of Islamic Religious Education and formulate its implications for strengthening the scientific framework of religious education that is adaptive to digital transformation. The study uses a qualitative approach with a literature study type. Data were obtained from journal articles, scientific books, and relevant academic documents through documentation techniques and analyzed using data reduction, thematic categorization, and conceptual interpretation. Data validity was maintained through literature triangulation and consistency of theoretical argumentation. The results show that Digital Neuroethics enables the reconstruction of the epistemology of Islamic Religious Education through the integration of revelation, reason, and digital experience as complementary sources of knowledge. This model positions revelation as an ethical orientation, reason as a critical instrument, and digital experience as a practical space for the formation of moral awareness. The implications of the research confirm the theoretical contribution in the form of developing an integrative epistemological paradigm as well as a practical contribution to strengthening the curriculum and learning strategies of Islamic Religious Education that are responsive to moral complexity in digital society.